DOAC‐Stop in lupus anticoagulant testing: Direct oral anticoagulant interference removed in most samples - Baker, Steven Andrew (Res Pract Thromb Haemost, 2021)
BACKGROUND: The use of direct oral anticoagulants (DOACs) is a convenient therapeutic option for patients at risk of thrombosis. DOACs interfere with clot‐based testing for the identification of lupus anticoagulant antibodies (LACs) in patients with antiphospholipid syndrome (APS), a common cause of acquired thrombotic disease. OBJECTIVES: To evaluate a commercially available reagent DOAC‐Stop for the removal of DOAC interference encountered in LAC testing. PATIENTS/METHODS: We collected a cohort of 73 test samples from patients on DOAC therapy identified at a large institutional coagulation laboratory from March to December 2019, along with samples from 40 LAC positive and negative control patients not on therapy. Samples were treated with DOAC‐Stop and tested for anti‐Xa activity and thrombin time for the removal of apixaban, rivaroxaban, argatroban, and dabigatran activity from patient samples. Treated and untreated samples were tested using the activated partial thromboplastin time, silica clotting time, and dilute Russell’s viper venom time to evaluate the reliability and utility of DOAC‐Stop. RESULTS: DOAC‐Stop markedly reduced DOAC interference from test samples (P < .05). DOAC‐Stop had no effect on LAC testing in the absence of DOAC therapy, permitting the identification of all LAC positive and negative controls. DOAC‐Stop removed false positives and false negatives resulting from DOAC interference and allows the identification of patients meeting criteria for the diagnosis of APS by LAC testing, as well as the detection of patients on rivaroxaban who are triple positive for APS. CONCLUSIONS: DOAC‐Stop is an effective adjunct for the clinical laboratory faced with DOAC interference in LAC testing.